2014
DOI: 10.15288/jsad.2014.75.968
|View full text |Cite
|
Sign up to set email alerts
|

Event-Specific Drinking in the General Population

Abstract: ABSTRACT. Objective: It has been well established that college students engage in heavy drinking during specifi c social events; however, within the general population, evidence of event-specifi c drinking has been largely indirect. The present study therefore aimed to investigate the temporal variability in daily alcohol consumption in the winter holiday months among residents of a large metropolitan area. Method: A random-digit-dialing telephone survey was conducted of residents who drank alcohol at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 20 publications
6
23
2
Order By: Relevance
“…However, whether the patient is admitted to a ward bed or occupies a 'trolley bed' in an ED observation ward, medical and nursing resources are still required to care for these patients. Contrary to the common belief that AAIs occur more commonly around festive periods, (18)(19)(20) our study found that AAIs peaked in April and May. This could be due to the increase in anti-drunk-driving media exposure and highly visible police enforcement with random alcohol breath screening testing, which usually takes place in December and January, around the major holidays, and relative lull in the middle of the year.…”
Section: Discussioncontrasting
confidence: 99%
“…However, whether the patient is admitted to a ward bed or occupies a 'trolley bed' in an ED observation ward, medical and nursing resources are still required to care for these patients. Contrary to the common belief that AAIs occur more commonly around festive periods, (18)(19)(20) our study found that AAIs peaked in April and May. This could be due to the increase in anti-drunk-driving media exposure and highly visible police enforcement with random alcohol breath screening testing, which usually takes place in December and January, around the major holidays, and relative lull in the middle of the year.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, across both groups, although at varying degrees, users exhibited a cyclic pattern of drinking whereby weekday drinking is lower, with increases on the weekends. This pattern of weekday to weekend drinking escalation is consistent with prior findings with college student and general population samples (e.g., Goldman et al, 2011; Hoeppner et al, 2012; Kushnir & Cunningham, 2014; Maggs et al, 2011). …”
Section: Discussionsupporting
confidence: 90%
“…Findings have shown that a greater portion of daily drinking variation is attributable to the intra-individual (within) versus inter-individual (between) level (Lau-Barraco, Braitman, Stamates, & Linden-Carmichael, in press). Nonstudent drinking tends to peak during holidays (Goldman, Greenbaum, Darkes, Brandon, & Del Boca, 2011; Kushnir & Cunningham, 2014) and on weekends (Kushnir & Cunningham, 2014), with weekday to weekend drinking increases being uniquely associated with social alcohol outcome expectancies (Lau-Barraco, Braitman, Linden-Carmichael, & Stamates, in press). Furthermore, in an effort to understand drinking patterns in nonstudent emerging adults, Cleveland and colleagues (2013) used latent class analysis to identify classes of alcohol users.…”
mentioning
confidence: 99%
“…These effects were specific to alcohol use and not observed for soda consumption. Numerous studies have revealed similar associations of AUDIT scores and weekends with alcohol use across a variety of populations (e.g., college students, nonstudent emerging adults; older adults; e.g., Kushnir & Cunningham, 2014;Lau-Barraco, Braitman, Linden-Carmichael, & Stamates, 2016;Sacco, Smith, Harrington, Svoboda, & Resnick, 2016;Tremblay et al, 2010). The clear correspondence replicated here supports the construct validity of data collection by revealing expected relationships for between-subject (i.e., AUDIT scores) and within-subject (i.e., weekends) predictors when using this novel data collection method.…”
Section: Discussionmentioning
confidence: 99%